The protein circPETH-147aa regulates metabolic reprogramming in hepatocellular carcinoma cells to remodel immunosuppressive microenvironment - Tian Lan; Fengwei Gao; Yunshi Cai; Yinghao Lv; Jiang Zhu; Hu Liu; Sinan Xie; Haifeng Wan; Haorong He; Kunlin Xie; Chang Liu; Hong Wu (Nature Communications)
Abstract Metabolic reprogramming fuels cancer cell metastasis and remodels the immunosuppressive tumor microenvironment (TME). We report here that circPETH, a circular RNA (circRNA) transported via extracellular vesicles (EVs) from tumor-associated macrophages (TAMs) to hepatocellular carcinoma (HCC) cells, facilitates glycolysis and metastasis in recipient HCC cells. Mechanistically, circPETH-147aa, encoded by circPETH in an m6A-driven manner, promotes PKM2-catalyzed ALDOA-S36 phosphorylation via the MEG pocket. Furthermore, circPETH-147aa impairs anti-HCC immunity by increasing HuR-dependent SLC43A2 mRNA stability and driving methionine and leucine deficiency in cytotoxic CD8+ T cells. Importantly, through virtual and experimental screening, we find that a small molecule, Norathyriol, is an effective inhibitor that targets the MEG pocket on the circPETH-147aa surface. Norathyriol reverses circPETH-147aa-facilitated acquisition of metabolic and metastatic phenotypes by HCC cells, increases anti-PD1 efficacy, and enhances cytotoxic CD8+ T-cell function. Here we show that Norathyriol is a promising anti-HCC agent that contributes to attenuating the resistance of advanced HCC to immune checkpoint blocker (ICB) therapies.